2013
DOI: 10.4103/1947-2714.123254
|View full text |Cite
|
Sign up to set email alerts
|

Acquired unilateral vocal fold paralysis: Retrospective analysis of a single institutional experience

Abstract: Background:Vocal cord paralysis continues to be an important issue in laryngology and is considered as a sign of underlying disease; the etiologies of this problem are varied and changing.Aims:The study was to carry out a retrospective analysis of patients with unilateral vocal fold paralysis diagnosed.Materials and Methods:The medical records of 53 patients diagnosed and treated for unilateral vocal fold paralysis were studied retrospectively. Data regarding age, sex, duration of symptoms, etiology, and side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…[7,8] Surgical trauma (21.6%) was found to be the second most common etiology in our study. The others were nonsurgical trauma (3.7%), nonlaryngeal malignancy (12.9%), central/neurological (6.1%), postradiation (0.3%), and other benign lesions (6.1%).…”
Section: Discussionmentioning
confidence: 95%
“…[7,8] Surgical trauma (21.6%) was found to be the second most common etiology in our study. The others were nonsurgical trauma (3.7%), nonlaryngeal malignancy (12.9%), central/neurological (6.1%), postradiation (0.3%), and other benign lesions (6.1%).…”
Section: Discussionmentioning
confidence: 95%
“…Treatment modalities were categorized as either voice therapy, laryngoplasty (for the purposes of this review, no distinction was made between injectable substances or type of framework surgery), and reinnervation. Of the 23 studies reporting etiology, n = 19 studies (66%) reported on patients with iatrogenic UVFP, which is reported in the literature as the most common etiology . Furthermore, of the 29 total studies, n = 18 (62%) reported on laryngoplasty (only) outcomes for the management for UVFP dysphonia.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 However there are various other studies proving either malignancy or iatrogenic as the major cause of uVCP. 1,11 Left cord was involved in 80% of the patients in our study. Although it was quantitatively higher in our study, it was consistent with other studies with respect to the side of involvement.…”
Section: Discussionmentioning
confidence: 99%